What is this thing called Journal of Audiovisual Translation? - Jankowska, Anna Magdalena; Di Giovanni, Elena; Kruger, Jan-Louis; Pedersen, Jan; Reviers, Nina; Romero-Fresco, Pablo (Journal of Audiovisual Translation, 2018)
We are proud to present the first issue of the Journal of Audiovisual Translation. Launching this new journal would not have been possible without the hard work of the Editorial Board members, much appreciated contributions from the Authors and support from ESIST and Scientific Board members. Audiovisual translation has come of age as a discipline in its own right and we strongly believe that it deserves a journal that is dedicated to this very specific field. Journal of Audiovisual Translation wishes to serve as an international forum and reference point for high-quality, innovative and in-depth research in all avenues of audiovisual translation studies.